Developments in nanogenerator-based human body motion energy harvesting systems - Yufei Han; Yani Kong; Bo Zhao; Cho Hong kwan; Shuze Sun (Alexandria Engineering Journal, 2025)
Recent advancements in nanogenerator-based human body motion energy harvesting systems have paved the way for self-powered wearable and implantable devices. This review explores the principles, materials, fabrication methods, and applications of piezoelectric and triboelectric nanogenerators for converting mechanical energy from human motion into electricity. We discuss the working mechanisms of these nanogenerators and highlight their unique advantages. The review examines a wide range of piezoelectric and triboelectric materials, including ZnO, BaTiO₃, PVDF, and PTFE, along with novel fabrication techniques such as hydrothermal synthesis and electrospinning. Innovative structural designs, including multilayer stacking and 3D architectures, have significantly enhanced energy harvesting efficiency and output power. The integration of nanogenerators into wearable sensors enables continuous, self-powered monitoring of human activities and physiological signals. Additionally, implantable nanogenerators show promise in powering medical devices and stimulating tissue repair, demonstrating excellent biocompatibility. Our analysis reveals that recent improvements in materials and designs have led to remarkable increases in power output, with some devices achieving power densities over 100 W/m². However, challenges remain in further improving energy conversion efficiency and long-term stability. With ongoing advancements, nanogenerator-based systems are poised to revolutionize self-powered wearable and implantable devices, promising significant progress in healthcare, fitness, and human-machine interactions.